2019
DOI: 10.33011/livecoms.1.2.11073
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Calculation of One-Dimensional Potentials of Mean Force [Article v1.0]

Abstract: The origins of different computational artifacts that may occur in the calculation of one-dimensional potentials of mean force (PMF) via umbrella sampling molecular dynamics simulations and manifest as free energy offset between bulk solvent regions are investigated. By systematic studies, three distinct causes are elucidated: (i) an unfortunate choice of reference points for the umbrella distance restraint; (ii) a misfit in probability distributions between bound and unbound umbrella windows in case of multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 96 publications
(160 reference statements)
2
20
0
Order By: Relevance
“…One possible reason for the slow PMF convergence in our work could be due to only distance restraint between the centre of mass (COM) of the peptide and the COM of the lipid bilayer (and not the orientation restraint of the peptide) was used during the umbrella sampling simulations. This agrees with a recent study by Markthaler et al [16] . who found that the standard umbrella sampling simulation of 1‐dodecanol binding to α‐cyclodextrin with orientation restraint on 1‐dodecanol only requires 20 ns simulations per umbrella window to achieve convergence, while the same simulation with only distance restraint between the COMs requires 140 ns per umbrella window for convergence.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…One possible reason for the slow PMF convergence in our work could be due to only distance restraint between the centre of mass (COM) of the peptide and the COM of the lipid bilayer (and not the orientation restraint of the peptide) was used during the umbrella sampling simulations. This agrees with a recent study by Markthaler et al [16] . who found that the standard umbrella sampling simulation of 1‐dodecanol binding to α‐cyclodextrin with orientation restraint on 1‐dodecanol only requires 20 ns simulations per umbrella window to achieve convergence, while the same simulation with only distance restraint between the COMs requires 140 ns per umbrella window for convergence.…”
Section: Resultssupporting
confidence: 91%
“…One possible reason for the slow PMF convergence in our work could be due to only distance restraint between the centre of mass (COM) of the peptide and the COM of the lipid bilayer (and not the orientation restraint of the peptide) was used during the umbrella sampling simulations. This agrees with a recent study by Markthaler et al [16] who found that the standard umbrella sampling simulation of 1-dodecanol binding to α-cyclodextrin with orientation restraint on 1-dodecanol only requires 20 ns simulations per umbrella window to achieve convergence, while the same simulation with only distance restraint between the COMs requires 140 ns per umbrella window for convergence. Although it is tempting to include orientation restraint on our peptides in the umbrella sampling simulations, it is, however, difficult to determine which initial orientation of the peptide relative to the lipid bilayer to be used, as different initial orientation may lead to different interaction energy with the lipid bilayer and hence its PMF value.…”
Section: Potential Mean Forcesupporting
confidence: 91%
See 1 more Smart Citation
“…The application to different non‐bonded force distance ranges is rather stable and relatively insensitive to the time between updates of the long‐ranged forces [78,79] . Of course, how well this approximation functions also depends on the system simulated and the property (thermodynamic, structural, dynamic, dielectric) of interest [57,58,61,62,78–80] . For an overview of the types of MTS algorithms we refer to [79] …”
Section: Molecular Simulation: Assumptions and Approximationsmentioning
confidence: 99%
“…Among the many possible methodological variants to compute binding free energies for host-guest systems within a rigorous thermodynamic framework [1], umbrella sampling (US) [2] has emerged as an easy-to-use approach that is supported by many publicly available pre-and post-analysis tools [3]. If certain artefacts related to insufficient sampling are accounted for [4], the method yields robust estimates. Based on our previous experience with this approach in the context of cyclodextrin host-guest systems [4], we aimed for the evaluation of the simulation protocol in the SAMPL8 challenge, featuring more complex guest molecules than considered before.…”
Section: Introductionmentioning
confidence: 99%